The validity and reliability of the Bahasa Malaysia version of the stop-bang questionnaire for identifying obstructive sleep apnea - Idris, Anuar Idwan (2017)
Introduction : Obstructive sleep apnea (OSA) is one the most major problem in otorhinolaryngology. It is characterized by repetitive episodes of shallow or paused breathing during sleep which is cause by complete or partial obstructions of the upper airway. OSA are common but rarely reported and addressed by primary health care providers. Among the risk factors for OSA are obesity, advanced age, male gender, neck circumference and family history and genetic predisposition. In diagnosing OSA, polysomnogram (PSG) remains the “gold standard”. However, this test takes time hence its waiting time increased. The STOP-Bang questionnaire (SBQ) is a self-administered, simple and validated questionnaire that detects OSA with high sensitivity which allows practitioners to prioritize the referral of patients at high risk of OSA to sleep disorders clinic. Objectives : To determine construct validity and reliability of Bahasa Malaysia (BM) version of SBQ by comparing to PSG and apply it in clinical setting as a screening tool for OSAMethodology : This is a cross sectional study done in Sleep Clinic of Hospital Universiti Sains Malaysia. Forward and backward translation of SBQ was done with presence of medical personnel and bilingual experts to produce the final BM version of SBQ. The final version was tested to 10 patients for a face vailidity. All 134 patients under our sleep clinic follow up completed a translated version of the STOP-Bang questionnaire in Bahasa Malaysia andunderwent a sleep study. The concurrent validity and reliability of the translated version of the questionnaire was tested against polysomnogram (PSG). Results : We observed 134 patients, mean age was 41.22 + 12.66 years old and 63.4% were male patients. Among all patients 28.4% had mild OSA, 33.6% had moderate OSA and 38.1% had severe OSA. A STOP-Bang score had sensitivity, specificity, positive and negative predictive value (PPV) for OSA of 61.42%, 71.05%, 84.06% and 41.54%, respectively. Conclusion : The Bahasa Malaysia version of STOP-Bang questionnaire is a powerful tool for stratifying patients in the diagnosis of OSA with acceptable sensitivity and specificity value.